Correlation of indicators of heart rate autonomic regulation and socio-economic well-being in young people 16–18 years old living in the Arctic zone of the Russian Federation - A. V. Ukhanova; L. V. Poskotinova (Acta Biomedica Scientifica)
Background. The impact of natural and climatic factors on human health may change under the influence of other factors related to his socio-economic well-being. The aim of the study. To determine the correlation between indicators of heart rate variability and parameters of socio-economic well-being, quality of life of young people living in the Arctic zone of the Russian Federation (Arkhangelsk).Materials and methods. Parameters of Heart rate variability in 36 young men (16–18 years old) were determined at entry (5 minutes) and at a fixed breath rate (5 minutes). We used the World Health Organization Quality of Life Brief Version of questionnaire, Family Affluence Scale (FAS II) and a questionnaire reflecting the financial situation, composition, and large number of children in the participants’ families.Results. According to correlation analysis, a decrease in the number of family vacations per year and FAS-II scores is accompanied by an increase in sympathetic activity. Indicators of self-perceived health status, number of cars in the family, FAS-II score and family financial status are positively correlated with indicators of vagal activity. Parameters of the psychological sphere of life quality and family composition were negatively correlated with sympathetic activity; parameters of the physical sphere of life quality and the number of family vacations per year were negatively correlated with vagal activity (fixed breath rate).Conclusion. We identified specific indicators of socio-economic well-being that are most closely related to both the tension of the cardiac activity mechanisms and the decrease in vagal reserves of autonomic regulation in young men living in the Russian Arctic.